2022
DOI: 10.3390/ani12233293
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Distribution of Runs of Homozygosity in Horse Breeds Representing Different Utility Types

Abstract: The present study reports runs of homozygosity (ROH) distribution in the genomes of six horse breeds (571 horses in total) representing three horse types (primitive, light, and draft horses) based on the 65k Equine BeadChip assay. Of major interest was the length, quantity, and frequency of ROH characteristics, as well as differences between horse breeds and types. Noticeable differences in the number, length and distribution of ROH between breeds were observed, as well as in genomic inbreeding coefficients. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…In our study, the ROH islet, including the QDPR and FAM184B genes, was found in the Soviet Heavy Draft horse breed, while in the work of Szmatoła et al, it was observed only in draft horses [33]. A homozygous region comprising the FGF5 gene, which are mutations that are associated with coat length in donkeys, has been found in American Standardbred horses [34] and is associated with the disease degenerative suspensory ligament desmitis [35].…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…In our study, the ROH islet, including the QDPR and FAM184B genes, was found in the Soviet Heavy Draft horse breed, while in the work of Szmatoła et al, it was observed only in draft horses [33]. A homozygous region comprising the FGF5 gene, which are mutations that are associated with coat length in donkeys, has been found in American Standardbred horses [34] and is associated with the disease degenerative suspensory ligament desmitis [35].…”
Section: Discussionsupporting
confidence: 43%
“…A gene belonging to the ZNF gene family, which plays a key role in the regulation of muscle growth and differentiation, was also found in ECA11. The discovered gene may be associated with selection pressure for strength, endurance, and a high percentage of muscle tissue, especially in draft breeds [33].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that same overlapping ROH segments between multiple individuals, so-called ROH islands, also highlight genetic regions that have been under selection, in cattle [ 7 , 8 ], sheep [ 9 11 ], and honeybees [ 12 ]. In horses, based on different genotyping platforms and ROH settings, numerous breed-specific ROH islands have already been identified that include genes associated with behaviour [ 13 , 14 ], coat colour [ 14 18 ], coat quality [ 19 ], fertility [ 13 , 18 22 ], size [ 15 , 22 ], skeletal development [ 18 , 19 , 23 ], muscle growth [ 24 ], geographical adaptations [ 14 , 25 ], and gait quality [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Horses have been selected based on conformation traits for centuries, resulting in diverse breeds with specific use (heavy type draught horses, light type sport horses, small ponies, etc.) 1 3 . Some traits, such as the concave (dished) head shape in the Arabian horse, are breed-specific and essentially aesthetic.…”
Section: Introductionmentioning
confidence: 99%